The Heterogeneous Effects of Early Track Assignment on Cognitive and Non-cognitive Skills - Maria Cotofan; Ron Diris; Trudie Schils (Tinbergen Institute, 2019)
Previous findings on (fleeting) relative age effects in school suggest that, given innate ability, too few younger and too many older students attend academic tracks. Using a regression discontinuity design around school-specific admission thresholds, we estimate the cognitive and non-cognitive effects of track assignment at the achievement margin, across relative age. We find that attending the higher track does not affect cognitive outcomes at any relative age. For older students, attending the higher track increases perseverance, need for achievement, and emotional stability. The results suggest that older students compensate lower ability (given high track attendance) with higher effort.
Keywords: J24; I21; 330; educational economics; school tracking; relative age; non-cognitive skills